2020
DOI: 10.1093/ageing/afaa045
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-prescription of oral anticoagulant treatment in non-valvular atrial fibrillation patients with dementia: a CPRD–HES study

Abstract: Abstract Dementia is a common comorbidity in patients with atrial fibrillation (AF) and treatment guidelines recommend oral anticoagulant (OAC) therapy for AF patients with dementia unless concordance cannot be ensured by the caregiver. Despite this, the literature reports a low prescribing of OAC treatment in these patients. This study investigated possible factors associated with non-prescribing of OAC treatment in dementia patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…Vulnerable older AF patients are frequently characterized by multimorbidity, polypharmacy, increased falling risk, frailty and dementia ( Jaspers Focks et al., 2016 ; Piccini et al., 2016 ; Steffel et al., 2016 ; Martinez et al., 2018 ; Rao et al., 2018 ; Alexander et al., 2019 ). Consequently, OACs tend to be inappropriately underdosed or discontinued in these patients subgroups ( Viscogliosi et al., 2017 ; Oqab et al., 2018 ; Madhavan et al., 2019 ; Proietti et al., 2019 ; Besford et al., 2020 ; Kapoor et al., 2020 ; Sanghai et al., 2020 ). However, even in AF patients ≥90 years old ( Raposeiras-Roubín et al., 2020 ), at high risk of falling ( Man-Son-Hing et al., 1999 ) or with dementia ( Orkaby et al., 2017 ; Subic et al., 2018 ), OAC continuation was still beneficial compared to omitting the OAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vulnerable older AF patients are frequently characterized by multimorbidity, polypharmacy, increased falling risk, frailty and dementia ( Jaspers Focks et al., 2016 ; Piccini et al., 2016 ; Steffel et al., 2016 ; Martinez et al., 2018 ; Rao et al., 2018 ; Alexander et al., 2019 ). Consequently, OACs tend to be inappropriately underdosed or discontinued in these patients subgroups ( Viscogliosi et al., 2017 ; Oqab et al., 2018 ; Madhavan et al., 2019 ; Proietti et al., 2019 ; Besford et al., 2020 ; Kapoor et al., 2020 ; Sanghai et al., 2020 ). However, even in AF patients ≥90 years old ( Raposeiras-Roubín et al., 2020 ), at high risk of falling ( Man-Son-Hing et al., 1999 ) or with dementia ( Orkaby et al., 2017 ; Subic et al., 2018 ), OAC continuation was still beneficial compared to omitting the OAC.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns have risen regarding the effectiveness and safety of NOACs in real-life clinical practice in patients with multiple comorbidities and concomitant medication use, especially vulnerable geriatric patients with AF who were largely underrepresented in these trials ( Lee et al., 2012 ). Consequently, NOACs tend to be underused or underdosed in these patients due to concerns of excessive fall-related intracranial bleeding, cognitive impairment with suboptimal therapy adherence, multiple drug-drug interactions (DDIs), low body weight or impaired renal function ( Viscogliosi et al., 2017 ; Oqab et al., 2018 ; Proietti et al., 2019 ; Madhavan et al., 2019 ; Besford et al., 2020 ; Kapoor et al., 2020 ; Sanghai et al., 2020 ). Therefore, there is an urgent need for a critical appraisal of the added value of NOACs in geriatric patients with AF at high thromboembolic and bleeding risk.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the follow‐up, 34.8% (220/632) and 39.1% (478/1222) of the reclassified and baseline high stroke risk patients, respectively, were not prescribed an OAC. Possible reasons for not prescribing an OAC in patients with high stroke risk, including high bleeding risk, frailty, use of antiplatelet agents, and dementia, are found elsewhere 29,30 . In our recent study using the MedicineInsight data set, we found that high risk of bleeding, having a recorded history of dementia or liver disease and female sex were independently associated with not being prescribed with an OAC 20 .…”
Section: Discussionmentioning
confidence: 95%
“…Possible reasons for not prescribing an OAC in patients with high stroke risk, including high bleeding risk, frailty, use of antiplatelet agents, and dementia, are found elsewhere. 29,30 In our recent study using the MedicineInsight data set, we found that high risk of bleeding, having a recorded history of dementia or liver disease and female sex were independently associated with not being prescribed with an OAC. 20 A recent study by Steinberg et al found that almost one-third of patients with high stroke risk and not prescribed an OAC had at least 1 major contraindication to OAC use; high bleeding risk was the most common contraindication.…”
Section: Discussionmentioning
confidence: 95%
“…Oral anticoagulants are used by many older individuals. Older people are at higher risk of developing dementia, and the use of oral anticoagulants among older people with dementia has been promoted 5 . Direct oral anticoagulants are also being used in patients with dementia 2,6 …”
Section: Introductionmentioning
confidence: 99%